2015
DOI: 10.1248/bpb.b15-00013
|View full text |Cite
|
Sign up to set email alerts
|

Osthole Upregulates BDNF to Enhance Adult Hippocampal Neurogenesis in APP/PS1 Transgenic Mice

Abstract: Adult hippocampal neurogenesis occurs in the dentate gyrus (DG) of the mouse hippocampus, and plays roles in learning and memory progresses. In amyloid precursor protein (APP)/presenilin 1 (PS1) transgenic mice, a rodent model of Alzheimer's disease (AD), severe impairment of neurogenesis in the dentate subgranular zone (SGZ) of the DG has been reported. Osthole, an active constituent of Cnidium monnieri (L.) CUSSON, has been reported to exert neuroprotective effects and may promote neural stem cell proliferat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 55 publications
(65 reference statements)
1
20
0
Order By: Relevance
“…Herein, we demonstrated a preventive effect after 6 weeks of Ost treatment from the age of 6–7 months in APP/PS1 mice, improving cognition and reducing many AD-associated biomarkers. The results indicated that Ost can significantly ameliorate the learning and memory deficits of mice by reducing the escape latency and the distance to goal, increasing the number of platform crossings and prolonging the time spent in the target quadrant (Figure 6) in the MWM test, consistent with previous reports (Liu et al, 2015). We also examined some biomarkers of AD in the hippocampus of APP/PS1 Tg mice, which is a neurogenesis area in the mammalian brain (Braak et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…Herein, we demonstrated a preventive effect after 6 weeks of Ost treatment from the age of 6–7 months in APP/PS1 mice, improving cognition and reducing many AD-associated biomarkers. The results indicated that Ost can significantly ameliorate the learning and memory deficits of mice by reducing the escape latency and the distance to goal, increasing the number of platform crossings and prolonging the time spent in the target quadrant (Figure 6) in the MWM test, consistent with previous reports (Liu et al, 2015). We also examined some biomarkers of AD in the hippocampus of APP/PS1 Tg mice, which is a neurogenesis area in the mammalian brain (Braak et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…77) It has been known that osthole can activate the BDNF/ TrkB signaling and affect the phosphorylation of cyclic AMP response element binding protein (CREB), which might be the underlying mechanisms of the enhancement of neurogenesis. 78) As we observed in the drug treatment group, the expression level of NF-M had been elevated, which relied on the powerful anti-apoptosis function of osthole. So far whether increasing the number of neuronal cells or reducing the apoptosis of neuronal cells can increase the expression of neuronal intermediate filament proteins is still obscure.…”
Section: Discussionmentioning
confidence: 63%
“…Cnidium monnieri APP/PS1 transgenic mice are rodent AD models with human APP and PS1 mutations and severe impairment of neurogenesis in the dentate subgranular zone of the dentate gyrus. Intraperitoneally administered osthole (30 mg/kg, PubChem SID: 253999366), an active constituent of the dried seeds of C. monnieri (Order: Apiales, Family: Umbelliferae, Genus: Cnidium), once daily for 28 days, can ameliorate the cognitive impairments in the dentate gyrus of hippocampus, and this function may be associated with stimulating BDNF/TrkB/CREB signal pathway [91]. [76], and AD and shows tremendous potential value in the treatment of nervous system disease.…”
Section: Curcuma Longamentioning
confidence: 99%